2019
DOI: 10.5433/1679-0359.2019v40n6supl3p3703
|View full text |Cite
|
Sign up to set email alerts
|

Levels of protected lysine and methionine in the diet of lambs: nutritional parameters and protein metabolites

Abstract: The objective of this study was to evaluate the effect of inclusion of different levels of protected lysine and methionine on the nutritional parameters and protein metabolites of lambs. The experiment was carried out at the Capim Branco Experimental Farm, at Uberlândia Federal University, during the months of September and October 2016. Five blood lambs ½ Dorper × ½ Santa Inês, approximately eight months old and with an average weight of 50 kg, were distributed in a Latin square scheme 5 × 5 (five treatments … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 7 publications
0
1
1
Order By: Relevance
“…Pôrto et al (2014), with the same cultivar, obtained total production of 1.79 kg plant -1 in the dose 331 kg ha -1 of N, dose higher than those studied in this study. On the other hand, the values were lower than those obtained by Araújo et al (2013), which using the recommended fertilization and the Aline hybrid, obtained a total yield of 3.6 kg plant -1 . It can be observed that in the researches where hybrids were used, the production was higher.…”
Section: Experiments 2 (2015)contrasting
confidence: 69%
See 1 more Smart Citation
“…Pôrto et al (2014), with the same cultivar, obtained total production of 1.79 kg plant -1 in the dose 331 kg ha -1 of N, dose higher than those studied in this study. On the other hand, the values were lower than those obtained by Araújo et al (2013), which using the recommended fertilization and the Aline hybrid, obtained a total yield of 3.6 kg plant -1 . It can be observed that in the researches where hybrids were used, the production was higher.…”
Section: Experiments 2 (2015)contrasting
confidence: 69%
“…According to Cardoso & Souza Neto (2016), the use of adapted hybrids results in greater yield potential, precocity, greater uniformity, better standardization and fruit quality, and stability of behavior under different environmental conditions. In addition to the genetic material, other factors that may influence the production of zucchini fruits are the growing season (Araújo et al, 2013), soil type, phytosanitary management and environmental conditions.…”
Section: Experiments 2 (2015)mentioning
confidence: 99%